Estudo de distintos processos oxidativos avançados eletroquímicos (e-POA) e teste de um reator solar em escala semi-piloto - Fernandes, Carlos Henrique Magalhães (2021)
In this work, two different advanced oxidation processes (AOP) were investigated: i) electrochemical processes (electro FeredFenton and photoelectro Fered-Fenton with BDD and DSA® electrodes under UVA/UVC irradiation (9 W) and ii) AOP based on solar radiation and using distinct oxidants (HOCℓ, H2O2, S2O82–, HSO5–) in the presence and absence of Fe2+ ions for the oxidation and mineralization of imidacloprid insecticide (IMDC: 50 mg L– 1). The FEF-Fered process, under UVA/UVC irradiation and HOCℓ/UVC with BDD and DSA®, respectively, had similar performances for the oxidation and mineralization of IMDC, reaching ~90% removal with an energy consumption of only ~0.3 kW hg–1. IMDC was readily oxidized when H2O2 concentrations of 50 and 100 mg L–1 (<30 min) compared to 25 mg L–1 (~90 min) were used. A similar behavior considering the removal of TOC was observed when using 50 (6.4 ±0.6 × 10–3 min–1) and 100 mg L–1 of H2O2 (5.91 ±0.04 × 10–3 min–1). High oxidation (100%; <30 min) and mineralization values (~9 × 10–3 min–1) were observed for the HOCℓ/UVC process in a wide pH range (3 to 6). The amount of electrogenerated oxidant (HOCℓ) for the HOCℓ/UVC process was determined and remained among 5 to 15 mg L–1. The HOCℓ/UVC process led to a more oxidizing chemical environment leading to the rupture of the IMDC imidazolic ring, in addition to dechlorination and hydroxylation reactions in all analyzed compounds. Such reactions were also observed for the FEF-Fered/UVA/Fe2+ process. Taking into account the main produced carboxylic acids, oxamic, succinic, formic and propionic acids were identified for the FEF-Fered/UVA/Fe2+ process, in addition to maleic, oxamic, malonic, glycolic, formic, acetic and dichloroacetic for the HOCℓ/UVC process. For the second investigated AOP based on solar radiation, all oxidants led to oxidation of IMDC in 3 h; however, removal levels of TOC were only significant when H2O2 and HOCℓ (~70% and ~60%, respectively) were used after 6 h. The use of Fe2+ (0.5 or 1.0 mmol L–1) did not show significant improvement in the oxidation and mineralization of IMDC.